Fishery waste valorization: Investigating Bacillus cereus fermentation condition for protease production - Muhammad Fadhlun Azim, Ab Rahman; Chua, Gek Kee; Noraziah, Abu Yazid; Siti Hatijah, Mortan; Rozaimi, Abu Samah; Chew, Few Ne (AIP, 2025)
Fish industries generate fish waste consisting of fish heads, bones, fins, tails, viscera, and scales. Fish waste has become the main contributor to the increasing biological waste problem that leads to water pollution, smell pollution and it also can cause diseases. Fish waste is rich with amino acids and protein sources that can be used as a low-cost nutritional substrate for fermentation, to turn the waste into value-added product such as protease enzyme. Protease enzyme has become an important substance in the industrial production of food, beverages, medicine, and leather products. The enzyme production through fermentation involves the use of microorganisms that rely on specific growth conditions to ensure the desired yield of product. In this study, the effects of the fermentation conditions, specifically medium pH (5.0 to 9.0) and agitation rate (100 to 300 rpm), on the protease production from Bacillus cereus (ATCC 10876) were investigated by using a shaker incubator. Fish waste hydrolysate with basal medium was used as the fermentation medium, which the hydrolysate was prepared by subjecting pre-treated fish wastes to acid hydrolysis. After the fermentation, the culture supernatant was analyzed for proteolytic activity and specific enzyme activity. This research study showed that fermentation conditions of medium pH and agitation rate had a major impact on the protease production. The proper agitating and medium pH play a crucial role in facilitating cell growth and enzyme formation during fermentation. The findings indicate that pH 6 and 150 rpm agitation were the best conditions for producing protease. The outcome offers valuable information for enhancing protease production by using fish waste hydrolysate and provides useful information for a variety of industrial applications.